Pengaruh Tingkat Utang, Pertumbuhan Penjualan, Intensitas Modal dan Risiko Perusahaan Terhadap Penghindaran Pajak - Ramadhani, Adrian Pasha; Nasution, Hafifah; Prihatni, Rida (Universitas Serambi Mekkah, 2024)
This study aims to determine the effect of leverage, sales growth, capital intensity, and company risk on tax avoidance. The population in this study were all properties real estate companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023, totaling 91 companies. Sampling in this study using purposive sampling technique, which is selecting samples according to the criteria so that 39 companies were obtained with 3 years of research and there were a total of 117 observations. The data analysis technique in this study uses descriptive statistical analysis, panel data regression analysis, classical assumption test, and hypothesis testing using Eviews 13 software. The test results show that the leverage and company risk has a positive and significant effect on tax avoidance practices, while sales growth and capital intensity have no effect on tax avoidance practices.